Effects of Interaction and Percolation on Topological Edge States - Zegarra Borrero, Antonio Federico (2021)
In this thesis we studied two important Topological Insulators (TIs), where we focused particularly on the role of interactions and percolation on the topological edge states. First, we analyzed the role of nearest-neighbor interactions in a prototype one-dimensional TI, namely the Su-Schrieffer-Heeger (SSH) model. Based on a Green s function formalism, we applied Dyson s equation in combination with T-matrix approximation to verify the bulk-edge correspondence in the presence of interactions. The critical exponents near topological phase transitions are found to be the same as the noninteracting SSH model, indicating that the system stays in the same universality class despite the presence of interactions. The second system is a two-dimensional timereversal symmetric TI, namely the Bernevig-Hughes-Zhang (BHZ) model in conjunction with a time-reversal breaking ferromagnetic metal (FMM), where we investigated the percolation of the quantum spin Hall state from the TI layer to the FMM by means of a tight-binding model. We demonstrated that depending on whether the edge state Dirac cone submerges into the FMM subbands and the direction of the magnetization of the FMM, the percolation of the edge state and its spin-momentum locking are affected in different ways. Surprisingly, we uncover that the equilibrium edge spin current in the BHZ model, naturally expected from the spin polarized propagating edge states, is in fact absent due to the cancellation from the valence bands. Nevertheless, laminar flows of room temperature persistent charge and spin currents are produced near the interface of the BHZ/FMM junction. Using a linear response theory, we investigate the current-induced spin polarization caused by the percolation of the edge state, which serves as a spin torque that is found to be predominantly field-like. Moreover, the spin polarization is dramatically enhanced near the impurities at the edge of the BHZ model.